PELAKSANAAN REVOLUSI MENTAL DI INDONESIA: KAJIAN DALAM KONTEKS PENDIDIKAN KEWARGANEGARAAN - Wildan Nurul Fajar (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
This study aims to obtain an overview of the mental revolution program inJokowi-JK Government viewed from the perspective of Civics. This research usedqualitative approach which descriptive method of analysis. Collecting data andinformation in research used study documentation and interview. From the results ofresearch known that the form of mental revolution is more done in the bureaucracy inthe form of coaching efforts to the State Civil Apparatus (ASN) in order to serve thecommunity as well as possible. The form of mental revolution in schools in the form ofSchool Introduction activities that contain mental revolution. While in universities inthe form of activities of KKN Thematic GNRM. The form of mental revolution in thecommunity is done through the cooperation of 13 components of society with ASN.Citizenship education is a major demand in the Mental Revolution because there is acivic virtue that can shape individual identity through citizenship.Keywords: civic educations,mental revolution